Transforming subsistence products to propellers of sustainable rural development: non-timber forest products (NTFPs) production and trade in Cameroon - Tieguhong, J.C.; Ndoye, O. (Lit Verlag, 2006)
This paper makes a desk review of the role of non-timber forest products (NTFPs) in the rural economy of Cameroon either as a safety net or as a subsector that can propel sustainable rural development and poverty alleviation. NTFPs are materials derived from forests, excluding timber and related wood products but including bark, roots, tubers, corms, leaves, flowers, seeds, fruits, sap, resins, honey, fungi, and animal products. They are collected from a wide range of ecotypes such as high forest, farm fallow, otherwise disturbed forest, and farmland for use as food, medicine, and trade. In some cases, they are the only means for local forest dwellers to participate in the cash economy (Sunderland et al, 2002: 1), especially with the collapse of the market prices of Cameroon’s primary export commodities such as cocoa and coffee. Recently, some NTFPs have emerged as non-conventional export commodities from Cameroon and the Central African region at large. Examples of such products include “Gnetum spp.”, “Irvingia spp.”, “Ricinodendron heudelotti”, and “Dacryodes edulis”. These products had a total import value of 8,648,000 FF (US$ 1,729,600) to Paris (France) alone in 1999 (Tabuna, 2000: 163). This paper explores the importance and potentials of NTFPs in poverty alleviation in the humid forest zone of Cameroon as well as highlights policy, technological, research and institutional weaknesses that may be strengthened for maximum benefits in rural areas. These development interventions may propel local economic growth that can be geared at strengthening rural communities’ capacity to better contribute to the millennium development goal of poverty alleviation.